2022
DOI: 10.1227/neu.0000000000002291
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Bone Quality Score Independently Predicts Proximal Junctional Kyphosis and/or Failure After Adult Spinal Deformity Surgery

Abstract: BACKGROUND:Proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) can be catastrophic complications associated with adult spinal deformity (ASD) surgery. These complications are markedly influenced by osteoporosis, leading to additional vertebral fracture and pedicle screw loosening. The MRI-based vertebral bone quality score (VBQ) is a newly developed tool that can be used to assess bone quality.OBJECTIVE:To investigate the utility of the VBQ score in predicting PJK and/or PJF (PJF/PJK) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…For example, Wang et al 27 demonstrated that higher VBQ scores were significantly associated with PJK risk after surgery for adolescent idiopathic scoliosis. These findings were then replicated in the adult spinal deformity population by Kuo et al 28 VBQ has also been demonstrated to be associated with pedicle screw loosening. Li et al 29 demonstrated a 4-fold increase in the rate of pedicle screw loosening in patients with high VBQ scores.…”
Section: Vbq = Median Si (L1-l4) ÷ Si (Csf)mentioning
confidence: 75%
“…For example, Wang et al 27 demonstrated that higher VBQ scores were significantly associated with PJK risk after surgery for adolescent idiopathic scoliosis. These findings were then replicated in the adult spinal deformity population by Kuo et al 28 VBQ has also been demonstrated to be associated with pedicle screw loosening. Li et al 29 demonstrated a 4-fold increase in the rate of pedicle screw loosening in patients with high VBQ scores.…”
Section: Vbq = Median Si (L1-l4) ÷ Si (Csf)mentioning
confidence: 75%
“…In one of these studies, a VBQ score threshold of 3.05 was found to be optimal for predicting pedicle screw loosing, with a sensitivity of 65.5% and a specificity of 71.3% 27 . Another study found that the VBQ score independently predicts proximal junction kyphosis and/or failure after adult spinal deformity surgery 29 …”
Section: Discussionmentioning
confidence: 99%
“…27 Another study found that the VBQ score independently predicts proximal junction kyphosis and/or failure after adult spinal deformity surgery. 29 Another potential use of VBQ-based bone quality analysis is predicting rates of pseudoarthrosis. There is currently no literature that describes using VBQ for this purpose, indicating a potential future direction to explore.…”
Section: Other Utilities Of Vbqmentioning
confidence: 99%
“…This score was later used by Soliman et al, 10 who found that the VBQ score was an independent predictor of cage subsidence after transforaminal lumbar interbody fusion. Subsequently, Kuo et al 25 found that the VBQ score independently predicted proximal junctional kyphosis when studying a thoracolumbar population. These successes in the lumbar spine led to the eventual adaptation of the VBQ score for the cervical spine in which the C-VBQ score was developed by Soliman et al 12 and was found to be an independent predictor of cage subsidence after ACDF procedures.…”
Section: Development and Application Of C-vbqmentioning
confidence: 99%
“…Although this was not the aim of this study, previous publications have demonstrated a significant relationship between the VBQ score and both imaging modalities. 12,25,27 Finally, no patients in the DJK cohort experienced compression fractures or instrumentation failure, which limits the ability to identify and analyze the causes of DJK within this cohort. Future prospective studies that are larger in scale should be completed to confirm the results of this study and investigate the correlation of DJK with patientreported outcome measurements and the incidence for the various causes of DJK to highlight possible areas of early intervention.…”
Section: Limitationsmentioning
confidence: 99%